Plankton community in Penaeus vannamei nurseries with synbiotic system under different frequencies of adjustment on Ca:Mg:K ratio in low salinity water - Otávio Augusto Lacerda Ferreira Pimentel; Valdemir Queiroz de Oliveira; Rildo José Vasconcelos de Andrade; Carlos Yure Barbosa de Oliveira; Elizabeth Pereira dos Santos; Alitiene Moura Lemos Pereira; Luis Otavio Brito; Alfredo Olivera Gálvez (Aquaculture and Fisheries)
The aim of this study was to evaluate plankton communities in Penaeus vannamei nurseries under different frequencies of adjustment on Ca:Mg:K ratio in low salinity water and with synbiotic system. A nursery culture was carried out for 40 days, using 2000 shrimp m⁻³. Following treatments were established: 1IA (Ca:Mg:K ratio adjustment to 1:3:1 on day 1); 2IA (Ca:Mg:K ratio adjustment to 1:3:1 on day 1 and day 20); 3IA (Ca:Mg:K ratio adjustment to 1:3:1 on day 1, day 10, and day 20); SW (seawater - salinity of 31 g L−1); and SWD (seawater diluted to a salinity of 2.3 g L−1). Rice bran processed by probiotic microorganisms was used as an organic carbon source. Treatments did not have a significant effect on phytoplankton and zooplankton composition. However, plankton composition was significantly different over the experimental course. A reduced abundance of Cyanophyta was observed compared to traditional aquaculture systems. This can be explained by the probiotic bacteria addition to the system, along with fertilization, which may have limited the growth of this harmful algae. Throughout the experiment, zooplankton community had a dominance by protozoan microorganisms, such as amoebae and ciliates. The presence of copepods and rotifers was also observed throughout the experimental course. This proves that the use of the synbiotic system provides conditions for the microbial loop development, mimicking a natural environment. Different adjustment frequencies in the water Ca:Mg:K ratio do not significantly change plankton composition in P. vannamei intensive nurseries using low salinity water and synbiotic system. Temporal variation in plankton composition probably occurred due to fertilization of the system with an organic carbon source. The use of the synbiotic system proved to be efficient in microbial loop development, providing the growth of a high load of microorganisms that can influence water quality and shrimp growth in low salinity water.